Provincializing Romanticism: Ottoman Hayaliyyun and Literary Globality in the Nineteenth Century. Issue 1 (1st June 2022) - Camoglu, Arif
Abstract : This essay considers the shortfalls of globalizing tendencies in nineteenth-century literary studies with a focus on the Ottoman Turkish articulation of romanticism, i.e., hayaliyyun . Retrieving a historically and geographically hybrid genealogy of romanticism through the Ottoman Turkish context, my discussion situates romantic imaginary and vocabulary back in the spatiotemporally dispersed, multilingual landscape where they emerged and evolved. As it seeks to move beyond the Euro-U.S.-centric frameworks employed in transnational accounts of romantic aesthetics, this article foregrounds linguistic difference and plurality as a conduit for rethinking globality in literary critical approaches to the nineteenth century.